IMPACT INVESTMENT MODELS TO SUPPORT THE ECONOMY IN UKRAINE - Shuplat, Olena (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
Abstract. The theses explore impact investing as a tool to support the economy of Ukraine in the context of war and post-war recovery. It is substantiated that such a model combines financial profitability with the achievement of measurable social and environmental effects. The key areas of application of impact capital are identified: infrastructure reconstruction, support for SMEs, energy sustainability, social entrepreneurship and regional development. The most suitable models for Ukraine are proposed, in particular, blended finance, impact funds and public-private partnership (PPP).